THE EFECT OF THE DIFFERENT COOKING METHODS ON THE QUALITY OF SHREDDED BARNACLE (Anadonta woodiana Lea) - Hoki Winda Lestari; N. Ira Sari; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The study aimed to determine the different cooking methods on the quality of shredded barnacle (Anadonta woodiana Lea). The methods used were cooking process consisting of three kinds which were: without cooking (D0), cooking with boiling technique (Dp), and cooking with steaming technique (Dk). The shredded barnacles were evaluated for organoleptic and chemical characters. The result showed that the best treatment to produce the highest quality of shredded barnacles was using of steaming technique. The organoleptic characteristic was shown as darkish brown appearance, shredded based and quite strong spices aroma and taste, and solid dry texture. It contained of 11,22 % moisture and 17,35% protein.Key-words:, barnacle, boiling, cooking, shredded, steaming